Intramodality and intermodality agreement in radiography and computed tomography of equine distal limb fractures. (28th June 2013) - Crijns, C. P.; Martens, A.; Bergman, H.‐J.; van der, H.; Duchateau, L.; van, H. J. J.; Gielen, I. M. V. L.
Summary Reasons for performing study Computed tomography (CT) is increasingly accessible in equine referral hospitals. Objectives To document the level of agreement within and between radiography and CT in characterising equine distal limb fractures. Study design Retrospective descriptive study. Methods Images from horses that underwent radiographic and CT evaluation for suspected distal limb fractures were reviewed, including 27 horses and 3 negative controls. Using Cohen's kappa and weighted kappa analysis, the level of agreement among 4 observers for a predefined set of diagnostic characteristics for radiography and CT separately and for the level of agreement between the 2 imaging modalities were documented. Results and conclusions Both CT and radiography had very good intramodality agreement in identifying fractures, but intermodality agreement was lower. There was good intermodality and intramodality agreement for anatomical localisation and the identification of fracture displacement. Agreement for articular involvement, fracture comminution and fracture fragment number was towards the lower limit of good agreement. There was poor to fair intermodality agreement regarding fracture orientation, fracture width and coalescing cracks; intramodality agreement was higher for CT than for radiography for these features. Potential relevance Further studies, including comparisons with surgical and/or post mortem findings, are required to determine the sensitivity and specificity of CT and radiography in the diagnosis and characterisation of equine distal limb fractures.